Billy Diamond: Strategist, Firebrand, and Visionary. - Feit, Harvey A. (Farringtonmedia, 2010)
Recalling a key moment of the Late Chief Billy Diamond's role in mobilizing James Bay Cree people's response to the James Bay hydro-electric project, and in the formation of Cree Nation political organizations.
Billy Diamond: stratège et visionnaire à la fougue légendaire.
Keywords: Billy Diamond; James Bay Hydro-electric Project; James Bay Cree; Waskaganish; Cree Nation; Grand Council of the Crees